Influência do treinamento resistido funcional sobre a modulação autonômica cardíaca, força muscular, parâmetros cardiorrespiratórios e qualidade de vida em mulheres jovens saudáveis - Barbosa, Marianne Penachini da Costa de Rezende [UNESP] (2014)
Introduction: Functional training promotes benefits over several muscle skills, however, its still unknown the effect on cardiac autonomic modulation, cardiorespiratory parameters and quality of life in adult healthy population. Objectives: To evaluate the influence of functional training on cardiac autonomic modulation, cardiorespiratory parameters, muscle strength and quality of life in healthy young women. Methods: Data were evaluated from 29 women who were divided in two groups: Functional Training Group (FTG, n = 13, 23 ± 2.51 years, body mass index (BMI) of 21.90 ± 2, 82Kg / m²) and Control Group (CG, n = 16, 20.56 ± 1.03 years, BMI 22.12 ± 3.86 kg / m²). The FTG performed functional training periodization for 12 weeks with a frequency of 3 times a week and a session duration of 60 minutes.Both groups underwent the following assessments before and after training: autonomic modulation, cardiorespiratory parameters, muscle strength (1RM test of each of the exercises used in training) and quality of life (SF-36 questionnaire). For assessment of autonomic cardiac modulation frequency was recorded beat to beat at rest in the supine position with spontaneous breathing for 30 minutes and indexes of heart rate variability (HRV) were obtained in the time and frequency by Kubios HRV software...